The Effects of Transit Systems on International Trade - Jerónimo Carballo; Alejandro Graziano; Georg Schaur; Christian Volpe Martincus (Center for Economic Studies and ifo Institute (CESifo), 2021)
In this paper, we estimate the trade effects of a transit system upgrading that streamlines border processing in developing countries. Our empirical approach combines transaction level export data from El Salvador with unique data that distinguishes export flows that were processed on the transit system. Our results indicate that the new transit system lowered regulatory border costs and raised exports. At the low end, our back-of-the-envelope estimate of the return to investment is US 3-to-1. The estimation results also suggest that existing frameworks that emphasize shipping frequency and the formation of new trade relationships are important to interpret trade facilitation policy. This evidence informs an important policy covered by the 2013 WTO Agreement of Trade Facilitation.
Keywords: F10; F13; F14; 330; transit trade; border effects; shipping frequency